Implementation of WebSocket in an IoT-Based Smart Home Door Security System Using ESP32-CAM with Face Recognition - Safriadi, Safriadi; Nasir, Muhammad; Erdiansyah, Umri (Politeknik Negeri Lhokseumawe, 2026)
The advancement of Internet of Things technology, especially in the field of information technology, opens up opportunities in the development of smarter, more efficient, and flexible home security systems. Frequently used systems such as fingerprints and RFID still have limitations in flexibility, scalability, and effectiveness against threats. To overcome these problems, an IoT-based home door security system was developed using ESP 32 - CAM and face recognition technology. This system utilizes the Haar Cascade Classifier algorithm for face detection and the Local Binary Pattern Histogram for face recognition. Test results show a fast response, communication stability, and an increase in accuracy of 66.07% with 10 datasets, 86.07% with 50 datasets, and 93.03% with 100 datasets. This shows that the more datasets used, the higher the system's accuracy in recognizing user faces.